COMPUTER SIMULATION OF TRAUMATIC MANDIBULAR FRACTURES IN CHILDREN OF DIFFERENT AGES - Yehorov, Rostyslav; Kopchak, Andrii; Kaniura, Oleksandr; Kryshchuk, Mykola (Eastern Ukrainian Medical Journal, 2026)
Introduction. The study of the mechanisms of traumatic bone destruction using computer-aided technologies is a pressing problem in modern medicine, particularly in maxillofacial surgery. It has not only diagnostic meaning, but also plays a major role in planning treatment measures. Materials and methods. The study was aimed at assessing the mechanisms of bone destruction in different age periods. A feature of the applied approach was the reconstruction of simulated lower jaw models based on multispiral computed tomography data of 4 patients aged 2, 6, 9, and 17 years, corresponding to different dentition periods. Results. When applying force to the chin area, the displacement of the model nodes was greater than when applying force to the body area. They were mainly caused by bending deformation in the area of both condylar processes and reached 3.7 mm for the 17-year-old lower jaw model. When reproducing a traumatic effect on the body of the lower jaw, the maximum displacement was also found in the model of a 17-year-old child and amounted to 2.4 mm, while the smallest displacement was recorded in the 9-year-old lower jaw model, which amounted to 0.8 mm. Conclusions. When studying the stress-strain state of the lower jaw of pediatric patients under the influence of external traumatic loads, it was found that in all studied age periods, when force is applied to the symphysis area, the stress-strain state of the bone is characterized by the formation of maximum stress concentration in the cortical layer of the bone in the area of the condylar processes. Calculations of external force extreme values for the studied lower jaw models with a strength limit of 100 MPa indicated that LJ fractures can occur under the impact applied to the chin with an amplitude from 247 N to 266 N for a 2-year-old and 9-year-old jaw models, respectively, and from 145 N – for a 6-year-old jaw model.